PERAN PEMERINTAH DESA DALAM PEMBANGUNAN DI DESA DODAP KECAMATAN TUTUYAN KABUPATEN BOLAANG MONGONDOW TIMUR - LOBBU, DORTEA NOVA; LENGKONG, FLORENCE DAICY; POMBENGI, JERICHO DANGA (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract : This research aims to know the role of Government in development in the village of Dodap sub-district ofTutuyan. This study uses qualitative methods with selected informants consisted of the village head/old/Sangadi Law,Secretary of the village, head of Development Affairs, head of BPD, head of Dusun, and local communities. Datacollection techniques used are interviews, observation and documentation. Qualitative data were analyzed withdescriptive narrative supported by primary and secondary data. The results showed that the associated role ofGovernment in development in the village of Dodap sub-district of Tutuyan has shown a fairly good results, in terms ofmaking new innovations in development, interaction and relationship building with community through socializationand the construction. It can be seen from the construction work training Hall, a cooperative village, smart village alsoworship facilities, and medical facilities and much more. In addition to counseling groups making the villagers by givingan explanation of the development of physical and nonphysical. Similarly, the ability of the Government in memanajand manage natural resources is already fairly well with how to increase self-reliance, dig the creativity of local resourceof the village in order to create a more productive village in processing the results of the source natural resources in asustainable way. In addition to that Government's role as a pioneer in the development of a Government which is alsoquite good also down directly to a location without intermediaries or without connecting, media and Governmentdirectly become a motivator in the work programme, the givers of guidance and direction for the community inparticipating actively in every development and also the Government coordinating direct factors that can push the paceof development and the granting of aid in the community. The development process undertaken by the Government inthe village of Dodap is quite good starts with creating a strategy and work plan according the decision of the team workof the village Dodap and align development village through the efforts against policies in building villagers in theautonomous region. But in terms of Government decision making is still impressed hesitation, lack of consistency withthe existing development planning and still less interaction with the community so that less Government know theexisting local resources and any development process so as to targetKey Words: The Role Of Government, Development, Development